Pengaruh Kepemilikan Manajerial, Struktur Modal dan Leverage terhadap Harga Saham - Tamba, Alpiner; Sidik, Solihin (The Double Entry Journal, 2022)
This study aims to determine the effect of managerial ownership, capital structure and leverage on stock prices. The research method used is quantitative with a descriptive and verification approach. The sample used is 30 data including 6 transportation companies listed on the Indonesia Stock Exchange for periode 2015 – 2019 with purposive sampling as sample selection technique. This research conclude that managerial ownership partially has a significant positive effect on the Stock Prices, while the capital structure and leverage partially has no effect on the stock prices of transportation companies listed on the IDX in the study period.